نموذج مقترح للأمن الصحي في مواجهة الأزمات غير المخطط لها: A Proposed Model for health Security in The Face of Unplanned Crises - حكيم بناولة (Journal of North African Economies, 2025)
The purpose of this study is to understand the difficulties encountered by Algeria’s health sector in relation to procedural research, as well as the status of relevant human resources under the risk management system and in response to unplanned health crises. The findings indicate that, despite the accessibility and free treatment of health care, the Algerian health sector remains among the laggards in the supply chains index. While the Algerian health sector ranks better in the rapid response to closure restrictions, it has a medium level in terms of health system accessibility. The study also resulted in a proposal for a study model based on the mentioned indicators. The study also advocated developing a healthy model based on selfsufficiency, establishing a strong position in global supply chains through solid relationships and resource diversification.